ELECTIVE TWIN REDUCTIONS: EVIDENCE AND ETHICS - Mcclimans, Leah (Bioethics, 2010)
Twelve years ago the British media got wind of a London gynecologist who performed an elective reduction on a twin pregnancy reducing it to a singleton. Perhaps not surprisingly, opinion on the moral status of twin reductions was divided. But in the last few years new evidence regarding the medical risks of twin pregnancies has emerged, suggesting that twin reductions are relevantly similar to the reductions performed on high-end multi-fetal pregnancies. This evidence has appeared to resolve the moral debate. In this paper I look at the role of clinical evidence in medical ethics. In particular I examine the role of clinical evidence in determining what counts as a significant harm or risk. First, I challenge the extent to which these empirical claims are descriptive, suggesting instead that the evidence is to some degree normative in character. Second, I question whether such empirical claims should count as evidence for what are essentially difficult ethical decisions – a role they appear to play in the case of elective reductions. I will argue that they should not, primarily because the value-laden nature of this evidence conceals much of what is ethically at stake. It is important to recognize that empirical evidence cannot be a substitute for ethical deliberation.